Penerapan Model Pembelajaran Talking Stick untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - Salsabila, Sabrina Putri; Gumala, Yosi (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2025)
This research aims to describe the talking stick learning model which is based on the findings of previous researchers, which were obtained from how much student learning outcomes increased after using the talking stick learning model. This research uses a literature study method by collecting 30 relevant journals from DOAJ, Sinta, Index Copernicus, Google Scholar and then using them as a literature review to identify them by reading, analyzing, categorizing, classifying and describing. The research results obtained from the analysis of the data found showed that student learning outcomes had increased significantly after implementing the talking stick model. This can be seen from several opinions which support that the talking stick model has an effect on improving student learning outcomes. So it can be concluded that the Talking Stick learning model can improve elementary school students' learning outcomes.